Resveratrol Supplementation Prevents Hypertension in Hypertensive Pregnant Rats by Increasing Sodium Excretion and Serum Nitric Oxide Level - Xiaowen Jia; Rong Zhang; Jinzhu Guo; Hua Yue; Qiuxia Liu; Lipei Guo; Qunchang Zhang (International Journal of Hypertension)
Background. Pregnancy-induced hypertension (PIH) remains a major cause of morbidity and mortality in pregnancy worldwide. This study was designed to study the blood pressure-lowering effect of resveratrol (RES) in a salt-induced hypertensive pregnant rat model. Methods. Forty female Sprague Dawley (SD) rats were randomized into 4 groups: Normal Preg (0.9% salt diet), Normal Preg + RES (0.9% salt diet plus daily oral RES for 4 weeks), Salt Preg (8% salt diet), and Salt Preg + RES (8% salt diet plus daily oral RES for 4 weeks). Noninvasive blood pressure was recorded on gestational days 7 and 14. On the gestational day 19, foetuses were weighed, and blood and urine samples were harvested for electrolytes and biochemical assays. Results. RES significantly reduced SBP, DBP, and MAP on gestational days 7 and 14 in the Salt Preg + RES group compared to the Salt Preg group (all P<0.05). Compared to the Salt Preg group, the foetal weight, serum NO level, urinary sodium, and 24 hour urine volume were significantly increased in the Salt Preg + RES group (all P<0.05). On the contrary, the levels of serum urea, serum creatinine, and urinary protein were significantly decreased in the Salt Preg + RES group compared to the Salt Preg group (all P<0.05). Conclusions. RES decreases blood pressure in a hypertensive pregnant rat model. Increasing sodium excretion and serum nitric oxide level might be, at least part of, the underlying mechanisms.